Relevansi Pengetahuan Dasa Samyojana Dalam Pendidikan Agama Buddha Dengan Peningkatan Moralitas - Sintia Sintia; Lauw Acep; Jo Priastana (Dhammavicaya : Jurnal Pengkajian Dhamma, 2020)
The research in this thesis was carried out using descriptive qualitative methods through literature studies, which took the source of religious books, scriptures, philosophy and general science in connection with the sources studied. Analysis technique is a step that must be done by researchers to obtain data. The data obtained is that Dasa Samyojana is still relevant in Buddhist education with an increase in morality. So, with the existence of the evidence shows that Buddhism was born with the education / teaching that was pioneered by the Buddha. The teaching process carried out has never been in conflict with the current teaching / education principles.